Systemic Sclerosis Associated Interstitial Lung Disease: New Directions in Disease Management - Mirsaeidi, Mehdi; Barletta, Pamela; Glassberg, Marilyn K. (Frontiers in Medicine, 2019)
A subgroup of patients with systemic sclerosis (SSc) develop interstitial lung disease (ILD), characterized by inflammation and progressive scarring of the lungs that can lead to respiratory failure. Although ILD remains the major cause of death in these individuals, there is no consensus statement regarding the classification and characterization of SSc-related ILD (SSc-ILD). Recent clinical trials address the treatment of SSc-ILD and the results may lead to new disease-altering therapies. In this review, we provide an update to the diagnosis, management and treatment of SSc-ILD.